The Infernal Devices: Clockwork Prince - Book 2 - Clare, Cassandra (New York : Margaret K. McElderry Books, 2011)
As the Council attempts to strip Charlotte of her power, sixteen-year-old orphaned shapechanger Tessa Gray works with the London Shadowhunters to find the Magister and destroy his clockwork army, learning the secret of her own identity while investigating his past.
Keywords: Paranormal fiction; Demonology -- Juvenile fiction; Orphans -- Juvenile fiction; Secret societies -- Juvenile fiction; Identity -- Juvenile fiction; London (England) -- Juvenile fiction -- History -- 19th century; Supernatural -- Fiction; Demonology -- Fiction; Orphans -- Fiction; Secret societies -- Fiction; Identity -- Fiction; London (England) -- Fiction -- History -- 19th century; Great Britain -- Juvenile fiction -- History -- Victoria, 1837-1901; Great Britain -- Fiction -- History -- Victoria, 1837-1901